2023
DOI: 10.3390/jpm13091409
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uric Acid in Human Health: Insights from the Uricase Gene

Youssef M. Roman

Abstract: Uric acid is the final product of purine metabolism and is converted to allantoin in most mammals via the uricase enzyme. The accumulation of loss of function mutations in the uricase gene rendered hominoids (apes and humans) to have higher urate concentrations compared to other mammals. The loss of human uricase activity may have allowed humans to survive environmental stressors, evolution bottlenecks, and life-threatening pathogens. While high urate levels may contribute to developing gout and cardiometaboli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Allantoin results from a ring-opening oxidation of the purine skeleton at the C-2 position, which improves water solubility. Animals with UOX improve renal elimination of products of purine catabolism compared to humans who lack UOX which can accumulate pathological levels of UA [ 32 ].…”
Section: Xor Biochemistrymentioning
confidence: 99%
“…Allantoin results from a ring-opening oxidation of the purine skeleton at the C-2 position, which improves water solubility. Animals with UOX improve renal elimination of products of purine catabolism compared to humans who lack UOX which can accumulate pathological levels of UA [ 32 ].…”
Section: Xor Biochemistrymentioning
confidence: 99%
“…[1][2][3][4] On the other hand, it has been proposed that the retention of UA represents an adaptive mechanism for human survival. 5 Indeed, the high UA blood levels observed in humans, in contrast to most other mammals, may have been an adaptive mechanism providing antioxidant capacity in situations of low availability of fruits and vegetables, 6 with UA accounting for about 50%-60% of antioxidants naturally present in humans. 7 Regarding clinical events, a U-shaped association of UA to cardiovascular events and all-cause mortality has been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous large epidemiological studies and their meta‐analyses have repeatedly shown a strong association between serum urate levels and several cardiovascular and metabolic disorders and risk factors 1–4 . On the other hand, it has been proposed that the retention of UA represents an adaptive mechanism for human survival 5 . Indeed, the high UA blood levels observed in humans, in contrast to most other mammals, may have been an adaptive mechanism providing antioxidant capacity in situations of low availability of fruits and vegetables, 6 with UA accounting for about 50%‐60% of antioxidants naturally present in humans 7 .…”
Section: Introductionmentioning
confidence: 99%